Pengaruh Kebijakan Keselamatan dan Kesehatan Kerja Terhadap Tenaga Kerja Konstruksi PT Wijaya Karya (Persero) Tbk. di Proyek Tol Surabaya Mojokerto - Radhitya Wisnu Satriawan; Togar Wiliater Soaloon Panjaitan (Jurnal Titra, 2016)
Occupational health and safety are one of important factor which can affect employees’ performance. The risk of accidents will rise if the company does not supervise the regulation of occupational safety and health policy. PT Wijaya Karya (Persero) Tbk. is pretty concern about this policy with the result of increased employees’ productivity. High employees’ performance will achieve high quality project target. This study uses questionnaire method that filled by construction employees to find the effect of occupational safety and health policy to construction employees performance. The data will be tested with double linear regression and hypothesis test. In addition, the author use simultaneous test (F test) and partial test (T test) for the hypothesis test. The double linear regression test result is occupational health variable has a bigger effect to employees performance that occupational safety. The simultaneously result is F has bigger value than Ftable, that means both of independent variables have a positive significant effect to construction employees performance. Furthermore, the partial test gives bigger T value than Ttable, which describes every independent variable have a positive significant effect to construction employees’ productivity.